2021
DOI: 10.1590/0004-282x-anp-2020-0517
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on patients with epilepsy

Abstract: Background: The COVID-19 pandemic and social distancing can have adverse impacts on adult people with epilepsy (PWE). Objective: To investigate the seizure frequency, the perceived well-being, and the presence of anxiety symptoms in PWE during the COVID-19 pandemic period. Methods: Data from a questionnaire on the repercussions of COVID-19 were analyzed in relation to the clinical variables of 114 PWE, with a significance level of p<0.05. Results: There were 26 cases of COVID-19 in PWE and/or family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…People with epilepsy are, overall, not considered to be at greater risk of COVID-19 infection or of developing a more severe form of the disease [12] , [13] , [14] , [15] , [16] , [17] , [18] . Other factors, including difficulty obtaining antiseizure medications (ASMs) and problems in accessing the health system, may play a role in worsening seizure control and exacerbating comorbidities in this group [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…People with epilepsy are, overall, not considered to be at greater risk of COVID-19 infection or of developing a more severe form of the disease [12] , [13] , [14] , [15] , [16] , [17] , [18] . Other factors, including difficulty obtaining antiseizure medications (ASMs) and problems in accessing the health system, may play a role in worsening seizure control and exacerbating comorbidities in this group [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Seizure worsening during COVID-19 pandemic has been reported by other workers also [3] , [12] , [13] , [16] , [17] , but report of worsening as well as improvement are also available [4] . Fonseca et al (2020) and Tedrus et al (2020) reported an increase in seizure frequency in almost 10% of PWE during the pandemic period [14] , [15] . As for factors associated with seizure worsening, sleep disorder, polytherapy and compliance issues were found to be related.…”
Section: Discussionmentioning
confidence: 98%
“…Depression in particular has been reported in a sizable proportion of PWE [7] , [8] , [9] , [10] and a bidirectional relationship between epilepsy and depression is suggested [11] . While many studies over the past one year have reported an increase in seizure frequency in PWE [3] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , however, to the best of our knowledge studies assessing the impact on depression in PWE are scarce. A few studies have evaluated the mental health of PWE i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the indirect infodemic impact, including socio-economic and psychological distress, can be more severe in PWE, particularly in patients with drug-resistant epilepsy (DRE), which can also lead to increased seizure frequency ( Alkhotani et al, 2020 , d'Orsi et al, 2004 , dos Santos Lunardi et al, 2021 , Hao et al, 2020 , Neshige et al, 2021 , Zarocostas, 2020 ). However, for some patients, the pandemic may have brought about a decrease in daily demands and stressors, eliminating the stress of the daily commute and other social obligations leading to decreased seizure frequency ( Neshige et al, 2021 , Reilly et al, 2021 , Rosengard et al, 2021 , Tedrus et al, 2021 ). Some studies have shown that a considerable proportion of PWE (8 to 31%) had an increase of seizure frequency during the pandemic related to an increase in stressors ( Sanchez-Larsen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%